An MDS 3.0 Distressed Behavior in Dementia Indicator (DBDI): A Clinical Tool to Capture Change. Issue 3 (30th November 2020) - Curyto, Kimberly J.; Jedele, Jenefer M.; Mohr, David C.; Eaker, April; Intrator, Orna; Karel, Michele
Abstract : Background/Objectives: Persons with dementia frequently demonstrate distress behaviors in dementia (DBD), associated with poorer outcomes. This study aimed to create a measure of DBD from routinely administered Minimum Data Set (MDS 3.0) behavior section items that demonstrated sensitivity to change, for evaluation of intervention efforts for VA Community Living Center (CLCs) residents exhibiting DBD. Setting: 72 VA nursing home settings, or Community Living Centers (CLCs). Participants: CLC residents with DBD (n = 302) were enrolled in an interdisciplinary behavioral intervention between 2013 and 2017. Design: A factor analysis of MDS behavior section items from assessments closest to baseline was conducted. Internal consistency, hypothesized associations between MDS factors and clinical measures, and sensitivity to detect change over time was explored. Measurements: Residents were assessed at baseline and post‐intervention using the MDS behavior section items and a validated clinical measure of DBD. Results: The Distress Behavior in Dementia Indicator (DBDI) was created as a consistent factor with internal consistency, and was related to a validated measure as predicted at baseline and post‐intervention. Sensitivity to change was demonstrated by using change score correlations ( r = 0.40–0.50), effect size ( d = 0.63), and reliable change indices. Conclusion: The DBDI is recommended for routine use in CLCs to evaluate impact of intervention effectiveness and provide quality improvement feedback.